2019
DOI: 10.1080/10826084.2019.1589522
|View full text |Cite
|
Sign up to set email alerts
|

Aggression and Anabolic–Androgenic Steroid Use Intent in Adolescents: A Longitudinal Study

Abstract: There is a dearth of longitudinal studies on risk factors for anabolic-androgenic steroid (AAS) use and intent. We conducted a longitudinal investigation of factors associated with AAS use intent from age 18 to 19, examining particularly the role of physical and verbal aggression. A sample of Norwegians completed questionnaires containing demographic, AAS use and intent, other addictions, aggression, and health measures at ages 18 (N = 1333, females = 58.9%) and 19 (N = 1277, females = 61.7%). The data were an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 72 publications
0
1
0
Order By: Relevance
“…Indeed, a recent meta-analysis of 12 randomized controlled trials has shown that among healthy males, AAS administration increases self-reported aggression (12). However, considering the inconsistency of results across studies (13)(14)(15)(16)(17)(18)(19)(20)(21)(22) it is not clear whether there are unobserved patterns of aggression and psychological distress among AAS users.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, a recent meta-analysis of 12 randomized controlled trials has shown that among healthy males, AAS administration increases self-reported aggression (12). However, considering the inconsistency of results across studies (13)(14)(15)(16)(17)(18)(19)(20)(21)(22) it is not clear whether there are unobserved patterns of aggression and psychological distress among AAS users.…”
Section: Introductionmentioning
confidence: 99%